2021
DOI: 10.1016/j.jaac.2020.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis: The Association Between Child and Adolescent Depression and Later Educational Attainment

Abstract: The association between depression and educational attainment in young people is unclear. This systematic review and meta-analysis examines the longitudinal association between depression and subsequent attainment, and its potential effect modifiers and mediators. Method: We searched Embase, PsycINFO, PubMed, ERIC, and the British Education Index from inception to October 23, 2019, conducted citation searching, and contacted authors for articles. Eligible studies reported on the longitudinal association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 69 publications
3
56
0
3
Order By: Relevance
“…Youth depression has considerable psychosocial implications, with depression in early adolescence predicting a higher probability of future unemployment, becoming pregnant, alcohol dependence, major depression, and other psychopathology (Clayborne et al, 2019; Fergusson & Woodward, 2002). There are also significant educational costs as is highlighted in a recent review by Wickersham et al (2020) who found lower levels of educational attainment associated with depression in children and adolescents irrespective of gender.…”
Section: Introductionmentioning
confidence: 99%
“…Youth depression has considerable psychosocial implications, with depression in early adolescence predicting a higher probability of future unemployment, becoming pregnant, alcohol dependence, major depression, and other psychopathology (Clayborne et al, 2019; Fergusson & Woodward, 2002). There are also significant educational costs as is highlighted in a recent review by Wickersham et al (2020) who found lower levels of educational attainment associated with depression in children and adolescents irrespective of gender.…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence suggests that a number of factors, including attainment, familial poverty, victimization and peer problems, and school connection, as well as other mental and physical health difficulties are related to problematic absenteeism (Kearney, 2008;May et al, 2021). Such factors have similarly been found to play an important role in internalizing symptoms (Shore et al, 2018;Wehmeier et al, 2010;Wickersham et al, 2021). Both models therefore adjusted for a number of baseline, time-invariant and time-varying covariates, as described below.…”
Section: Covariatesmentioning
confidence: 99%
“…Dari semua kemampuan dan kebutuhan itu dapat ditingkatkan melalui latihan fisik dan mental yang teratur. Banyak orang yang bisa berenang tetapi hanya sebatas renang biasanya, dan tidak menggunakan teknik yang semestinya dilakukan (Wickersham et al, 2020).…”
Section: Pembahasanunclassified